Peranan Kepercayaan Konsumen sebagai Variabel Mediasi dalam Meningkatkan Komitmen Konsumen berbelanja secara online di Jakarta - Hasyim (Jurnal Aplikasi Manajemen, 2013)
The purpose of this article is to present the role of consumer trust as a mediator variable between consumer perceived value, and company reputation for building the customer commitment in online shopping behaviour. Data was collected via self-administered questionnares from a purposive samples drawn from the population of online consumers with focus on Jakarta area. The results of statistical analysis shows that consumer trust is a key factor in development of costumer commitmen on online shopping means Customer Commitment can be developed by developing the perceived value and company reputation via Consumer Trust. This study and their results have several limitation and indicate direction for further research.